Vinyl Sulfoxonium Ylide: A New Vinyl Carbenoid Transfer Reagent for the Synthesis of Heterocycles - Vaitla, Janakiram; Bayer, Annette; Hopmann, Kathrin H. (Synlett, 2019)
Sulfoxonium ylides have recently gained prominence as safe carbenoid precursors in metal-catalyzed reactions. The stability and reactivity of sulfoxonium ylides depend on the substitution of the ylide carbon. The reactivity of vinyl-substituted sulfoxonium ylides is different and offers several advantages over known stabilized sulfoxonium ylides in the case of carbenoid transfer reactions. Herein, we provide an overview of early efforts in this area, with particular emphasis on our own recent development of sulfoxonium ylide-derived vinyl carbenoid transformations for N-Heterocycles.1 Introduction2 Classification of Sulfoxonium Ylides3 Synthesis of Vinyl Sulfoxonium Ylides4 [3+2] Annulation of Vinyl Sulfoxonium Ylides5 [4+1] Annulation of Vinyl Sulfoxonium Ylides6 Conclusion
Keywords: sulfoxonium ylides; metal carbenoids; transition-metal catalysis; insertion reactions; heterocycles